Effects of a brief interpersonal conflict cognitive reappraisal intervention on improvements in access to emotion regulation strategies and depressive symptoms in college students. Issue 10 (2nd October 2020) - Rodriguez, Lindsey M.; Lee, Katherine D. M.; Onufrak, James; Dell, Jaclyn B.; Quist, Michelle; Drake, Hunter P.; Bryan, Jennifer
Abstract: Objective: Research has demonstrated relative success with brief interventions that utilize social psychological theory to target the root cause of unwanted behaviours. Given the intersections among anxious attachment, depression, and emotion dysregulation, the current research utilises an interpersonal conflict cognitive reappraisal intervention to evaluate improvements in depressive symptoms. We also evaluated mediation via improvements in emotion regulation and moderation by attachment anxiety. Design: Undergraduates ( N = 260) completed a baseline assessment and were randomised to one of four writing conditions: An interpersonal conflict from (a) their own perspective; (b) the other party's perspective; or (c) a neutral, third-party perspective (primary experimental condition) or about their day (control condition). They also completed a follow-up survey online two weeks later. Main outcome measures included limited access to emotion regulation strategies and depressive symptoms. Results: Consistent with hypotheses, compared to control, participants who adopted the perspective of neutral third party reported improvements in access to emotion regulation strategies. There was also a significant indirect effect on depressive symptoms through changes in strategies. Finally, improving strategies led to a reduction in depressive symptoms, especially for those higher in attachment anxiety. Conclusion: We present promising emerging results for a single-session, conflict-focused, brief cognitive reappraisal intervention on changes in emotion regulation and depressive symptoms.